Publisher Correction: Interrelationship between daily COVID-19 cases and average temperature as well as relative humidity in Germany - Naleen Chaminda Ganegoda (Nature Portfolio, 2021)
The original PDF version of this Article contained a repeated error where the Blackboard Bold 1 symbol was incorrect in Equations 1 and 2.